Experimental and numerical study of heat transfer to nanofluid flow in sudden enlargement of annular concentric pipe / Hussein Togun Abdullah - Hussein Togun, Abdullah (2015)
Turbulent heat transfer to separation nanofluid flow in annular concentric pipe has been studied numerically and experimentally. In numerical study, finite volume method with standard k-ε turbulence model in three dimensional domains is used. Three different types of water based (Al2O3, CuO, TiO2) nanofluids have been employed in this simulation. The adopted boundary conditions were expansion ratio (ER= 1.25, 1.67, and 2), Reynolds number ranging from 20000 to 50000, and Al2O3, CuO, TiO2 water based nanofluids with volume fractions varied between 0 to 2% at heat flux varied from 4000 W/m2 to 16000 W/m2. For experimental study, Al2O3 water based nanofluid was used to validate numerical results. The outer cylinder of downstream section was heated by uniform heat flux whereas the outer cylinder of upstream section and the overall length of the inner cylinder were unheated. The results show that the volume fraction of nanofluid and Reynolds number significantly affect the surface heat transfer coefficient; an increase in surface heat transfer coefficient was noted when both volume fraction of nanofluids and Reynolds number were increased for all the cases. The peak of the heat transfer coefficient had occurred after the sudden expansion moved far from the step height with the increase of sudden expansion dimensions due to separation flow in case of both pure water and nanofluid. It has been noted from the counter of streamline the size of recirculation zone increased with the increases of Reynolds number and expansion ratio. Increase of volume fraction of nanofluid enhances the heat transfer coefficient due to augmented heat transport by nanoparticles in base fluid which raises the convection heat transfer. The lowest pressure drop and maximum thermal performance are observed at Reynolds number 50000, 2% Al2O3 water based nanofluid at expansion ratio 2 in comparison to others. The improvement of heat transfer was about 36.6 % for pure water at expansion ratio 2 compared to heat transfer obtained in straight pipe. Augmentation of heat transfer could be achieved by using nanofluid at expansion ratio 2 where the total improvements were about 45.2% (TiO2), 47.3 %(CuO), and 49 %(Al2O3). Also the increment in the pressure drop was about 42% for pure water at expansion ratio 2 compared with straight pipe whereas by using nanofluid they were 62.6% (TiO2), 65.4% (CuO), and 57.6% (Al2O3). Good agreements were observed between numerical and experimental results all the way. Extension studies on thermal performances and pressure drop for separation flow over single or double and Forward or Backward-Facing steps have also been performed. Studies were conducted numerically with different models for flowing water and different types of nanofluids. Here heat transfer and pressure drop enhancements were observed following the similar trend obtained for sudden expansion configuration.